Prevalence of altered cervical cytological pattern: Aretrospective study in females visiting tertiary care hospital - Dr. Roopam K Gidwani; Dr. Falguni J Goswami; Dr. Nirali V Shah; Dr. HP Srilakshmi; Dr. Gena K Ramchandani; Dr. Bansari L Chawada (Tropical Journal of Pathology and Microbiology, 2018)
Background: Cervical cancer is one of the major causes of morbidity and mortality in India. Pap smear is a simple, non-invasive, cost-effective and sensitive tool to detect various non-neoplastic and neoplastic lesions of cervix. The objective of this study was to estimate the prevalence of cervical cytological pattern in a tertiary care centre; by using conventional Papanicolaou (Pap) smears for the screening of inflammatory, premalignant and malignant lesions of the cervix. Methods: This cross-sectional study is based on 574 patients who attended the out‑patient Department of Obstetrics and Gynecology, during the period between Jan 2015 to Feb 2017. Pap smears were prepared from patients presenting with complaints like vaginal discharge, post‑coital bleeding, inter‑menstrual bleeding, dyspareunia, and pain in lower abdomen. Conventional Papanicolaoustained smears were classified as per Bethesda 2001 nomenclature. Results: Prevalence of altered cervical cytological pattern was 75.59% amongst females visiting hospital. A total of 574 cervical pap smears were studied, out of which 66 were inadequate. Out of 508 cases, 448 cases were of NILM [including 324 (63.78%) inflammatory lesions and 124 (24.41%) normal smears] and 60 (11.81%) cases of epithelial lesions. The epithelial lesions prevalence rate was ASCUS (5.7%), LSIL (1.4%) and HSIL (1.4%), AGUS (0.78%), SCC (0.6%) and endometrial carcinoma (0.2%). Conclusions: This study shows relatively high prevalence of epithelial abnormalities with increasing age, parity, women with clinical lesions on per speculum findings. Malignancy was more common in sixth and seventh decade and intraepithelial lesions/dysplasia was seen mostly in fourth and fifth decade. Inflammatory lesions were more common in younger age group. Pap smear should be advised as a routine screening procedure; as it is a simple, cheap, safe and practical diagnostic tool for early detection of cervical cancer in high risk group population. It also helps in diagnosis of inflammatory lesions including the identification of causative organism and atrophic changes.